173k views
1 vote
Please help guys lol I have no clue how to do this... it’s the square root method?

Please help guys lol I have no clue how to do this... it’s the square root method-example-1

1 Answer

1 vote

Answer:

2 seconds.

Explanation:

s=16t² -- (1)

s=64. (given)

Put value of s in (1)

64=16t²

16t²=64

t²=64/16

t²=4

t=√4

t=2 seconds.

Hope this helps :-)

User Adedoy
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.